TENDENCIES TOWARDS VIOLENT BEHAVIOR IN ISLAMIC COLLEGE STUDENT - Yuarini Wahyu Pertiwi; Aninda Nur Haliza; Hanni Pratiwi; Unaisah Kultsum Lasyena; Muhamad Haudhi Al-Azzah; Triana Malenita Dewi; Miranti Entahna Anugeraya; Ambar Nurdian Syaputri; Vanis Adelia; Idup Sapitri; Dhimas Fachri; Lintang Meiheswara SG; Nabila; Lulu Maharani Rafita; Novita Sari (Journal of Islamic Psychology and Behavioral Sciences, 2023)
This research to find out whether the behavior of current students still has a tendency to commit physical and sexual violence. The subjects in this study amounted to N = 139, determined by purposive sampling technique. The research method used in this study is using a survey or questionnaire distributed online to several universities in Indonesia. We developed a scale that had been made by José A. Ruiz-Hernández and David Pina, et al. from the University of Murcia, Spain, with the title of their researchAttitudes towards School Violence Questionnaire, Revised Version: CAHV-28. The results we got from the analysis using Statistical Product and Service Solutions (SPSS) were 19 subjects or 14%. students are at a high level, as many as 96 subjects or 69% of students are at a moderate level and as many as 24 subjects or 17% of students are at a low level. Based on gender, men tend to commit violence than women because they have a mean value = 56.9, greater than women, namely 51.6. Meanwhile, based on age, those aged 21 years and over tend to commit violence because they have a mean value = 56.61, followed by those aged 17-18 years, namely 52.95 and the last is 19-20 years old, namely 52.16.